Pengaruh Fasilitas Kerja Dan Kemampuan Komunikasi Aparat Terhadap Kualitas Pelayanan Publik Di Desa Kanaungan Kecamatan Labakkang Kabupaten Pangkajene Dan Kepulauan - Wahyuni Wahyuni; Edi Jusriadi; Sitti Nurbaya (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This study aims to determine and analyze the Influence of Work Facilities and Communication Skills of Apparatus on the Quality of Public Services in Kanaungan Village, Labakkang District, Pangkajene and Kepulauan Regency. This type of research is quantitative. The data collection method used is observation and distribution of questionnaires to respondents, namely the community. The sampling data collection technique uses the Slovin formula. The data analysis technique used is multiple linear regression analysis. Based on the results of statistical calculations through the statistical for the social sciences (SPSS) application regarding work facilities and communication skills of civil servants on the quality of public services in Kanaungan Village, Labakkang District, Pangkajene and Kepulauan Regency, the author draws the conclusion that work facilities and communication skills of civil servants have a positive and significant effect on the quality of public services.